Islamic Education Mentoring Program and the Religiousity of Prospective Accountant - Hafiez Sofyani; Mahartika Retno Febri Anggraini; Sabrina Ayunani (Universitas Islam Negeri Raden Mas Said Surakarta, 2016)
This study aims to examine differences in the level of ethical sensitivity and commitment of religiosity among prospective accountants pursuing Islamic Education Mentoring Program and those who are not. Samples were accounting students at the University of Muhammadiyah Yogyakarta. To test the hypothesis, this study had carefully applied non-parametric test different techniques, namely the Mann Whitney and Kruskal Wallace. The study states that there are differences in the level of ethical sensitivity of students who take the program and who are not. Commitment religiosity of students who take the program and those who are not has found no statistical difference. Gender differences also take effect on the sentivity level of ethical and commitment of religiousity.Keywords: religiousity, accountant, ethical sensitivity, commitment